Policy Regime Decay. Issue 1 (28th December 2020) - Sheingate, Adam
Abstract : This paper develops the concept of policy regime decay to examine what happens when the political foundations of public policies break down. Policy regime decay consists of an erosion of consensus over policy goals, an unraveling of support coalitions, and an exhaustion of institutional capacity to structure the policy process. These elements of decay have observable implications and they inform an empirical strategy for a case study of U.S. food and agriculture policy. Using content analysis of congressional hearings, analysis of legislative roll calls, and policy agenda measures, the paper finds evidence of elite disagreement over nutrition programs, a partisan divide on Farm Bill votes, and a diffusion of committee jurisdiction over food and agriculture issues in Congress. These findings have implications for understanding the policy consequences of polarization, policy feedback effects, and the dynamics of policy regimes. 摘要: 本文提出"政策制度衰败"（policy regime decay）的概念，以分析当公共政策的政治基础瓦解时会发生什么。政策制度衰败由三者组成：政策目标共识的损坏、支持联盟的瓦解、搭建政策过程架构的制度能力的枯竭。这三要素具有可见的影响，并且影响了一项关于美国粮食与农业政策案例研究的实证策略。通过对国会听证会、点名投票分析、政策议程措施进行内容分析，本文发现，国会政治精英在营养计划上意见不一、农业法案投票出现党派分歧、粮食和农业问题上存在委员会司法权扩散。这些研究发现对理解极化的政策结果、政策反馈效应、以及政策制度动态而言具有意义。 Resumen: Este artículo desarrolla el concepto de decadencia del régimen de políticas para examinar qué sucede cuando se derrumban los fundamentos políticos de las políticas públicas. El deterioro del régimen de políticas consiste en una erosión del consenso sobre los objetivos de las políticas, el desmoronamiento de las coaliciones de apoyo y el agotamiento de la capacidad institucional para estructurar el proceso de políticas. Estos elementos de descomposición tienen implicaciones observables e informan una estrategia empírica para un estudio de caso de la política alimentaria y agrícola de EE. UU. Utilizando el análisis de contenido de las audiencias del Congreso, el análisis de las listas legislativas y las medidas de la agenda de políticas, el documento encuentra evidencia de desacuerdo entre las élites sobre los programas de nutrición, una división partidista en los votos de la Ley Agrícola y una difusión de la jurisdicción de los comités sobre temas de alimentación y agricultura en el Congreso. Estos hallazgos tienen implicaciones para comprender las consecuencias políticas de la polarización, los efectos de retroalimentación de las políticas y la dinámica de los regímenes políticos.